Changes in facial expressions during short term emotional stress as described by a Facial Action Coding System in horses - Lundblad, Johan (SLU/Dept. of Clinical Sciences (until 231231), 2018)
Animals subjected to stress is a well-known issue that has to be taken into account when working in a clinical environment. A stress response is closely related to several physiological and behavioural effects that could potentially mask symptoms of pain. So far, research has focused on evaluating stress using ethograms or physiological indicators. However, little has been focused on using facial expressions when evaluating stress. This is important because only a little research regarding facial expressions of pain has considered the potential of other emotions affecting the readings. Therefore, this thesis discusses the concepts of pain and stress and how they work together, as well as methods for objectively evaluate pain and stress, using literature available today.